Comparison of external versus endoscopic dacryocystorhinostomy (Annals of Medical Research, 2021)
Aim: To compare the complications, operative features and results of external and video- endoscopic endonasal DCR performed from January 1st, 1995 to January 1st, 1999. Methods: External DCR with or without silicone tube intubation by Dupuy-Dutemps- Bourget technique was performed on 79 unilateral dacryocystitis patients (66 women and 13 men) in group 1 and endoscopic endonasal hammer-chisel DCR utilizing hammer-chiesel removal of bone located over the lacrimal sac on 51 eyes of 36 cases, 33 women and 3 men (15 bilateral patients) in group 2.
Keywords: Dacryocystorhinostomy, external, endoscopic, hammer-chiesel